2023
DOI: 10.1002/acn3.51730
|View full text |Cite
|
Sign up to set email alerts
|

MRI and fluid biomarkers reveal determinants of myelin and axonal loss with aging

Abstract: Objective: White matter damage is a feature of Alzheimer's disease, yet little is known about how facets of the Alzheimer's disease process relate to key features of white matter structure. We examined the association of Alzheimer's disease (Aß 42/40 ratio; pTau181), neuronal injury (NfL), and reactive astrogliosis (GFAP) biomarkers with MRI measures of myelin content and axonal density. Methods: Among cognitively normal participants in the BLSA and GESTALT studies who received MRI measures of myelin content (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…A previous study has reported a relationship between myelin water fraction (MWF), a surrogate of myelin content, and p-tau181/Aβ 42 ratio in the CSF from preclinical AD patients, in which higher levels of p-tau181/Aβ 42 resulted in an increased decline in MWF with age [ 63 ]. Also, elevated plasma p-tau181 has been associated with lower axonal density quantified by MWF in the occipital lobe [ 64 ]. These reports suggest that increased levels of fluid p-tau181 correlate with reduced myelin content in human brains.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study has reported a relationship between myelin water fraction (MWF), a surrogate of myelin content, and p-tau181/Aβ 42 ratio in the CSF from preclinical AD patients, in which higher levels of p-tau181/Aβ 42 resulted in an increased decline in MWF with age [ 63 ]. Also, elevated plasma p-tau181 has been associated with lower axonal density quantified by MWF in the occipital lobe [ 64 ]. These reports suggest that increased levels of fluid p-tau181 correlate with reduced myelin content in human brains.…”
Section: Discussionmentioning
confidence: 99%
“…However, further studies are needed to investigate these patterns of change in other structural brain measures and their relationship to plasma p‐tau181. Also, investigating the association of these measures with glial fibrillary acidic protein (GFAP), a product of astroglial activation and astrocytosis, might clarify these findings, as this biomarker has been associated with incipient axonal loss in CU individuals 1,2,15,46 . Another possible explanation is that older adults with reduced cortical thickness and hippocampal atrophy are more closely related to clinically significant cognitive impairment.…”
Section: Discussionmentioning
confidence: 99%
“…We used the signal model explicitly accounting for nonzero TE. 6,16,20 This emerging method offers rapid and reliable whole-brain MWF map within feasible clinical time 6,16,20,[31][32][33][34] and has been used in assessing myelin loss in mild cognitive impairment and dementias, as well as examining factors influencing cerebral myelination in normative aging. 16,22,23,26,[32][33][34][35][36][37][38][39][40][41][42][43][44][45] A whole-brain R1 map was also generated from the co-registered SPGR and DAM datasets using DESPOT1, 21 and a wholebrain R2 map was generated from the co-registered bSSFP and DAM datasets using DESPOT2.…”
Section: Data Processingmentioning
confidence: 99%
“…6,16,20 This emerging method offers rapid and reliable whole-brain MWF map within feasible clinical time 6,16,20,[31][32][33][34] and has been used in assessing myelin loss in mild cognitive impairment and dementias, as well as examining factors influencing cerebral myelination in normative aging. 16,22,23,26,[32][33][34][35][36][37][38][39][40][41][42][43][44][45] A whole-brain R1 map was also generated from the co-registered SPGR and DAM datasets using DESPOT1, 21 and a wholebrain R2 map was generated from the co-registered bSSFP and DAM datasets using DESPOT2. 21 The DW images were corrected for eddy current using the function eddy in FSL and for motion effects using the affine registration tools as implemented in FSL 30 and registered to the DW image obtained with b=0 s/mm 2 using FNIRT.…”
Section: Data Processingmentioning
confidence: 99%